Differences in otolith shape and fluctuating‐asymmetry between reared and wild gilthead seabream (Sparus aurata Linnaeus, 1758). Issue 1 (19th October 2020) - Geladakis, George; Somarakis, Stylianos; Koumoundouros, George
Abstract: Otolith structure is a useful tool in discrimination among fish populations as it is a permanent record of the influence of endogenous and exogenous factors. In the present study we examined otolith morphology and fluctuating asymmetry (FA) for differences between wild‐caught (by bottom trawl) and reared specimens of Gilthead seabream ( Sparus aurata ). Based on the frequency of regenerated scales (degree of scale regeneration, SRD) on each specimen, a threshold of 30% SRD was used to assign wild‐caught fish individuals as wild (≤30% SRD, LR group) or as possible aquaculture escapees (>30% SRD, HR group). Based on the analysis of elliptic Fourier descriptors, significant differences were found in otolith shape between reared (Rr) and the wild‐caught groups (LR, HR). Reared fish had otoliths with significantly larger perimeter (OP ) than wild‐caught fish. Furthermore, FA was significantly higher in the Rr than the LR group for OP and all except one shape descriptors (harmonics 2–7). The HR group exhibited intermediate levels of FA between the low and high FA levels observed in the LR and Rr groups. Results are discussed in terms of the value of combining otolith and scale morphology for the identification of escapees in wild Gilthead seabream stocks.